Peran Strategis Penguatan Kontrak Psikologis Dan Wawasan Kepemimpinan Pada Siswa Sekolah Menengah Ata - Amiruddin Siahaan, Muamar Al Qadri, Poniman Adyanto, Darno (Cybernetics: Journal Educational Research and Social Studies, 2023)
This study has two objectives, namely to describe the implementation of learning leadership by principals in improving student learning outcomes. This is a qualitative research that produces descriptive data in the form of written or oral words from people and observable behavior. This research applied interview, observation and documentation in collecting the data. For analyzing the data, this research used a nonstatistic method, namely descriptive data analysis. It means that the data obtained through research on the implementation of learning leadership by principals and is reported as it is. Then, the data were analyzed descriptively to get an overview of the facts. Based on the results of research conducted in MAN 2 Langkat, it can be concluded that the principal is the most important element in improving the quality of education. To be able to improve the quality of education, principals must conduct good learning leadership. The implementation of learning leadership in MAN 2 Langkat in terms of the learning leadership model expressed by Hallinger and Murphy is divided into three dimensions, namely through the formulation of school missions, management of good learning and creating a conducive school climate. These three dimensions are then specified into eleven descriptors.